2020
DOI: 10.1111/ijcp.13473
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever is associated with increased risk for ischaemic heart disease and mortality–Perspective derived from a large database

Abstract: Aims of the study Familial Mediterranean fever (FMF) is a hereditary, auto‐inflammatory disease, characterised by recurrent, self‐limiting attacks of fever with inflammation of the serosal membranes, joints, and skin. Chronic inflammation was previously associated with increased risk for ischaemic heart disease (IHD). However, the association between FMF and IHD remains unclear. The objective of this study is to determine whether this association exists. Methods Utilising the database of the largest health‐car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Increased aortic stiffness, measured by PWV while the preoperative anesthetic evaluation, is related with more pronounced hypotension during the induction [1,15]. Structural changes like smooth muscle hypertrophy, changes of extracellular matrix and increased collagen levels of the vessel wall seems to be cause of reduced arterial elasticity in increased blood [3].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased aortic stiffness, measured by PWV while the preoperative anesthetic evaluation, is related with more pronounced hypotension during the induction [1,15]. Structural changes like smooth muscle hypertrophy, changes of extracellular matrix and increased collagen levels of the vessel wall seems to be cause of reduced arterial elasticity in increased blood [3].…”
Section: Resultsmentioning
confidence: 98%
“…Chronic immune and inflammatory diseases can present many complex problems for the cardiology, cardiothoracic surgery and anesthesiology practice. Rheumatoid arthritis (RA) and familial Mediterranean fever (FMF) are related with increased risk of cardiac events [1]. Endothelial dysfunction, which is also an early stage of atherosclerotic process, is associated with chronic inflammation [2].…”
mentioning
confidence: 99%
“…The risk of CVD has been demonstrated to be higher in chronic rheumatic diseases, including ankylosing spondylitis, psoriatic arthritis, and rheumatoid arthritis, than in the general population in a significant number of studies [ 37 , 38 , 39 ]. However, whether or not there is an increased risk for CVD in FMF patients is a matter of some dispute, since there are limited data on the risk of CVD in patients with FMF and also in patients with AA amyloidosis secondary to FMF and other autoinflammatory diseases [ 18 , 19 , 40 ]. In a recent study, mortality related to CVD was found to be 2.8-fold higher in patients with FMF-amyloidosis than in patients with other chronic kidney diseases [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As inflammatory diseases increase the risk of CVD, traditional CVD risk factors should be more rigorously identified and controlled in subjects with autoimmune and inflammatory diseases, especially those with active inflammation and higher mortality rates such as FMF. However, whether there is an increased risk for coronary artery disease (CAD) in FMF patients is a subject of some debate [ 18 , 19 ]. In a retrospective study in the Sicilian population, harboring the M694V allele increased the risk of developing myocardial infarction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…QTc interval prolongation is also associated with increased mortality among patients with acute myocardial infarction [ 24 ]. Indeed, Gendelman et al have demonstrated that FMF patients are at increased risk of mortality due to ischemic heart diseases, echoing the importance of QTc interval as a prognostic factor for FMF patients [ 25 ].…”
Section: Reviewmentioning
confidence: 99%